PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA BERBASIS ANDROID PADA POKOK BAHASAN GEJALA PEMANASAN GLOBAL UNTUK PEMBELAJARAN FISIKA DI SMA - Indah Kurnia Nur Pratiwi Guterres; Sudarti Sudarti; Maryani m; Pramudya Dwi Aristya Putra (FKIP Universitas Jember, 2018)
AbstractThis research was a developmental research. The product of this research was inthe use of an android -based snake and ladders as a learning media on the topic of globalwarming phenomenon in senior high schools. This research were developed by Borg andGall method that modified into 5 step: (1) study literature, (2) planning, (3) designing (4)validation and revision, and (5) testing media and final revision.The results showed thatthe use of an android -based snake and ladders as a learning media can be valid,practically anf effective for use. This can be seen from the validation assesment criteriagets valid with a assesment scores reached 4,552. The practically assesment showed frompercentage 93,33 % with a criteria practice indicating that the media was good for useaccording with the teacher implementation planned learning and also showed frompercentage 80,64 % with a criteria practice indicating that study activity learning washigh. The effectiveness assesment showed from improvement student learning outcomeswith the average of N-gain score was 0,73 which was in the high category.Keywords: effectiveness, practicality, android based snake and ladder, validity